Diversity of Staphylococcus aureus Isolates in European Wildlife - Monecke, Stefan; Gavier-Widén, Dolores; Hotzel, Helmut; Peters, Martin; Guenther, Sebastian; Lazaris, Alexandros; Loncaric, Igor; Müller, Elke; Reissig, Annett; Ruppelt-Lorz, Antje; Shore, Anna C.; Walter, Birgit; et al. (PloS one, 2016)
Staphylococcus aureus is a well-known colonizer and cause of infection among animals and it has been described from numerous domestic and wild animal species. The aim of the present study was to investigate the molecular epidemiology of S. aureus in a convenience sample of European wildlife and to review what previously has been observed in the subject field. 124 S. aureus isolates were collected from wildlife in Germany, Austria and Sweden; they were characterized by DNA microarray hybridization and, for isolates with novel hybridization patterns, by multilocus sequence typing (MLST). The isolates were assigned to 29 clonal complexes and singleton sequence types (CC1, CC5, CC6, CC7, CC8, CC9, CC12, CC15, CC22, CC25, CC30, CC49, CC59, CC88, CC97, CC130, CC133, CC398, ST425, CC599, CC692, CC707, ST890, CC1956, ST2425, CC2671, ST2691, CC2767 and ST2963), some of which (ST2425, ST2691, ST2963) were not described previously. Resistance rates in wildlife strains were rather low and mecA-MRSA isolates were rare (n = 6). mecC-MRSA (n = 8) were identified from a fox, a fallow deer, hares and hedgehogs. The common cattle-associated lineages CC479 and CC705 were not detected in wildlife in the present study while, in contrast, a third common cattle lineage, CC97, was found to be common among cervids. No Staphylococcus argenteus or Staphylococcus schweitzeri-like isolates were found. Systematic studies are required to monitor the possible transmission of human- and livestock-associated S. aureus/MRSA to wildlife and vice versa as well as the possible transmission, by unprotected contact to animals. The prevalence of S. aureus/MRSA in wildlife as well as its population structures in different wildlife host species warrants further investigation.